دراسة دور أذيات عنق الرحم في حدوث انبثاق الأغشية الباكر (Latakia University Journal -Medical Sciences Series, 2018)
مقدمة : يحدثُ انبثاق الأغشية الباكر بتمام الحمل في 10 % من الحمول تقريباً , في حين يختلط ما بين 3 – 5% من الحمول بحدوث انبثاق الأغشية الباكر قبل تمام الحمل . هدف البحث : دراسة دور أذيات عنق الرحم في حدوث انبثاق الأغشية الباكر(PROM) المواد و الطرق : إن هذه دراسة حالة – شاهد أجريت في قسم التوليد و أمراض النساء في مشفيي الأسد و تشرين الجامعي , اللاذقية , سوريا , في الفترة الممتدة ما بين كانون الثاني 2015 و حتى تموز 2017 .                                                                                     تكونت مجموعة الحالة من 90 مريضة انبثاق الأغشية الباكر مع قصة أو فحص سريري يقترح أذية رضية في عنق الرحم بعد استبعاد عوامل الخطورة التقليدية للانبثاق الباكر . تكونت مجموعة الشاهد من 50 سيدة حامل أكملت حملها بشكل طبيعي دون حدوث PROM . النتائج : تحدث النسبة الأكبر من حالات انبثاق الأغشية الباكر قبل الأسبوع 37 من العمر الحملي . تحدث الولادة في غضون 24 ساعة لدى 85% من مريضات انبثاق الأغشية الباكر بتمام الحمل PROM و لدى 49.2% من مريضات انبثاق الأغشية الباكر قبل تمام الحمل PPROM . هناك علاقة هامة بين وجود سوابق ولادة منزلية من قبل طاقم طبي غير كفؤ , سوابق ولادة عسيرة , تمزّق سابق في عنق الرحم و الخزعة المخروطية و حدوث إنبثاق الأغشية الباكر (P0.05). الخلاصة : تشكل أذية عنق الرحم سبباً هاماً لانبثاق الأغشية الباكر و يجب توعية جميع الحوامل حول ضرورة الرعاية الطبية حول الولادة . Introduction : Premature rupture of membranes (PROM) occurs in 10% of pregnancies , while 3-5% of pregnancies are complicated with Preterm rupture of membranes (PPROM) . Aim : To study the role of uterine cervix injuries in PROM . Materials and Methods :This is a case-control retrospective study conducted at Obstetrics and Gynecology Department at Al-Assad and  Tishreen University Hospitals , Lattakia , Syria , during the period between January 2015 – July 2017 . The case group consisted of 90 PROM patients with a history or a physical examination suggesting a cervical traumatic injury after exclusion the traditional risk factors of premature rupture of membranes, The control group consisted of 50 healthy pregnant women who successfully completed the pregnancy without PROM. Results : Most premature rupture of membranes cases occur before 37 gestational age . Delivery within 24 hours occurs in 85% of PROM cases and 49.2% of PPROM cases . There is a significant relation between prior home delivery , difficult delivery , uterine cervical tearing and conization of uterine cervix and the incidence of premature rupture of membranes(P0.05) . Conclusion : Uterine cervix injury is a major cause of premature rupture of membranes . All pregnant women should be educated about the importance of perinatal medical care .